Analisis Penerapan Akuntansi Aset Biologis pada Usaha Peternakan Ayam Broiler Ditinjau dari Prespektif Islam - Wahyuni, Lia Wulan; Susilowati, Lantip (Lembaga Yasin AlSys, 2022)
Animal husbandry related fields. Many animals are raised by humanis including chickens. Broiler chicken farming provides very promising benefits for breeders. Chicken is including in the biological assets regulated in PSAK 69. Mr Fatkhur established a business in the field of broiler chicken farming, which was named Barokah Farm, having his address at Gandusari district Trenggalek. The recording and preparation of financial reports carried out at Barokah Farm have not referred to PSAK 69 as a whole. Regarding the preparation of financial reports, it is very useful for chicken farming business actors, especially regarding the expenditure of needs during the process of selecting chicken seeds to selling broiler chicken to consumers. Descriptive or qualitative methods are used in this study. The data collected in this study were conducting interviews with Barokah Farm owners, observing objects before they were investigated and then documented. Questions asked by the researcher to Mr Fatkhur regarding the measurement, disclosure, recognition and preparation of financial statements at Barokah Farm. The result of the study show that the recording of financial statements at Barokah Farm is very simple and can only be understood by the Barokah Farm owner. While outsiders cannot understand the financial statements made at Barokah Farm. In Islamic, chicken farming is allowed and even recommended to fulfill daily life. In the Islamic perspective, it is very necessary to process the halalness of an item that will be used or consumed by many people.